Pengaruh Motivasi dan Persepsi pada Matematika Terhadap Prestasi Belajar Matematika Mahasiswa PGSD Universitas Quality Berastagi - SIMBOLON, NOVI TARI (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2022)
This study is the result of measuring students' motivation, perception and achievement in learning mathematics using a quantitative approach with multiple regression techniques. The sample in this study were all 32 students of class 11A22, 32 students at Quality Berastagi University, PGSD study program. Data on the level of students' motivation and perceptions were obtained through a questionnaire, while data on mathematics learning achievement was obtained from the results of the mathematics test on the subject of cubes and blocks. From the research results obtained information that the learning motivation of 37.5% of students included in the low category. Students' perception of mathematics is 34.4% of students in the medium category. While the average student achievement shows a pretty good achievement, as many as 37.5% of students. The influence of students' motivation and perceptions of mathematics on student achievement in mathematics is indicated by a coefficient of determination of 0.76. This shows that the percentage of the contribution of the influence of students' motivation and perception on mathematics to mathematics learning achievement is 76%. So the motivation and perception of students together have a significant effect on the mathematics learning achievement of 11A22 students at Quality Berastagi University, PGSD study program.